Millennium Development Goals as an instrument of sustainable development in developing countries - Przemysław Deszczyński (Journal of Agribusiness and Rural Development, 2011)
During Millennium Summit in 2000 in New York, 189 member countries of the United Nations accepted Millennium Declaration. It contains Millennium Development Goals which are a form of road map for realization of development aid based on sustainable development in developing countries. The article discusses this problem.